Endoscopic Ultrasonography-Guided Fine-Needle Aspiration for Duodenal Subepithelial Lesions Showing a Hypoechoic Mass on Endoscopic Ultrasound Imaging - Akahoshi, Kazuaki; Akahoshi, Kazuya; Shiratsuchi, Yuki; Tamura, Shinichi; Uemura, Kento; Sashihara, Reiichi; Ohishi, Yoshihiro; Inoue, Kanako; Koga, Tadashi; Koga, Hidenobu (Turkish Journal of Gastroenterology, 2023)
Background/Aims: For duodenal subepithelial lesions showing a hypoechoic mass on endoscopic ultrasound imaging, the utility of endoscopic ultrasound-guided fine-needle aspiration and the frequency of histological types have not been the focus of previous literature. This study aimed to clarify this. Materials and Methods: This prospective observational study enrolled 22 consecutive patients who underwent endoscopic ultrasoundguided fine-needle aspiration for duodenal subepithelial lesions with hypoechoic mass on endoscopic ultrasound. Immunohistochemical analysis was performed for all endoscopic ultrasound-guided fine-needle aspiration and surgically resected specimens. The main outcome measures were the technical results of endoscopic ultrasound-guided fine-needle aspiration and the frequency of histological types of duodenal subepithelial lesions with hypoechoic mass. Results: Thirteen fine-needle aspiration specimens were obtained from the duodenal bulb and eight from the descending duodenal region. The puncture was not performed because of intervening vessels in one patient. The diagnostic rate was 81% (95% confidence interval: 58.1-94.6, 17/21 patients). In 12 patients receiving surgical resection (excluding one cancellation of endoscopic ultrasoundguided fine-needle aspiration), the diagnostic accuracy of endoscopic ultrasound-guided fine-needle aspiration was 75% (95% confidence interval: 42.8-94.5, 9/12 patients). No complications were observed. The histopathological diagnoses included 11 cases of gastrointestinal stromal tumor (50%), 2 cases of leiomyoma (9%), 2 cases of metastatic cancer (9%), 2 cases of benign inconclusive, and 1 case each of carcinoid, malignant lymphoma, leiomyosarcoma, gauzeoma, and aberrant pancreas (4.5% each). The frequency of malignant tumors in the duodenal subepithelial lesions with hypoechoic mass group was 73% (16/22 patients). Conclusions: Endoscopic ultrasound-guided fine-needle aspiration for duodenal subepithelial lesions with hypoechoic mass was safe and accurate. As duodenal subepithelial lesion with hypoechoic mass has a reasonably high possibility of containing malignant tumors, it is desirable to perform endoscopic ultrasound-guided fine-needle aspiration. Cite this article as: Akahoshi K, Akahoshi K, Shiratsuchi Y, et al. Endoscopic ultrasonography-guided fine-needle aspiration for duodenal subepithelial lesions showing a hypoechoic mass on endoscopic ultrasound imaging. Turk J Gastroenterol. 2023;34(11):1156-1162.